Imbalanced distribution of group 2 innate lymphoid cells (ILCs) and ILC precursors in peripheral blood of patients with primary biliary cholangitis. (3rd April 2022) - Li, Haolong; Zhan, Haoting; Cheng, Linlin; Yan, Songxin; Wang, Li; Li, Yongzhe
Abstract: Innate lymphoid cells (ILCs), a novel group of innate immune cells, play a key role in the early immune response via rapidly reacting to signals expressed by tissue‐resident cells. ILCs contribute to some autoimmune diseases. We aim to investigate the proportions of circulating ILC subgroups in patients with primary biliary cholangitis (PBC). Overall, 48 patients with PBC and 24 healthy controls (HCs) were enrolled. Circulating ILCs and cytokine production were detected by flow cytometry. The proportions of total ILCs, ILC precursors (ILCPs) and ILCP/ILC2 ratio increased and that of ILC2s decreased in patients with PBC. ILC2 proportion was negatively correlated with gamma‐glutamyl transpeptidase (GGT), alanine aminotransferase (ALT) and aspartate aminotransferase (AST). The proportion of ILCPs and ILCP/ILC2 ratio were positively correlated with alkaline phosphatase, GGT, ALT and AST. ILC2 proportion was significantly decreased in the ursodeoxycholic acid (UDCA) ‐non‐responder group compared with the UDCA‐responder group, whereas the proportion of ILCPs and ILCP/ILC2 were ratio significantly increased. The proportions of CD38 + ILC2s, CD38 + ILCPs, CD45RO + ILC2s and CD45RO + ILCPs were significantly higher in patients with PBC than in HCs. Levels of IL‐17A producing ILCs were higher in patients with PBC than in HCs. PBC is accompanied by alterations in circulating ILCs. The proportions of ILC2s, ILCPs, and ILCP/ILC2 ratio were associated with the PBC disease activity. The proportions of ILCPs and ILCP/ILC2 ratio may reflect the UDCA treatment failure in patients with PBC. ILC2s and ILCPs from patients with PBC get activated, these cells may be involved in the pathogenesis of PBC.